Pengaruh Influencer Marketing dan Conten Marketing Dimediasi oleh Online Customer Review Kepada Keputusan Pembelian - Erni Irmawati; Marno Nugroho (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze and identify the influence of Influencer Marketing and Content Marketing, mediated by Online Customer Review, on purchasing decisions. Competition in the beauty product industry is becoming increasingly intense due to the large number of brands circulating in the market. The research population consists of consumers who have purchased The Originote products in the Semarang area. The sample includes 100 respondents with the criteria of having purchased The Originote products at least twice and being students, university students, or workers. Data collection was carried out by distributing questionnaires to The Originote product consumers in the Semarang area. The testing in this study employed the Partial Least Squares Structural Equation Modeling (PLS-SEM) method for analysis. This research is expected to provide benefits to the field of knowledge and serve as a reference for the beauty industry in understanding the factors influencing consumers’ purchasing decisions